Cloning and characterization of an envelope-specific probe from xenotropic murine leukemia proviral DNA. - Buckler, C E (1982)
An 8.9-kilobase EcoRI restriction fragment was cloned from mink cells chronically infected with NFS-Th-1 xenotropic murine leukemia virus by using a lambda phage host vector system. After its transfer into pBR322, the EcoRI DNA insert was characterized and found to contain 6.7 kilobases of proviral DNA sequences and 2.2 kilobases of mink cellular DNA flanking the 5' end of the viral genome. A 500-base pair fragment which was located at the 3' terminus of the cloned DNA insert and which mapped to the env region of xenotropic proviral DNA was subcloned into pBR322. This xenotropic envelope proviral DNA segment did not hybridize to ecotropic murine leukemia proviruses but did anneal to representative alpha and beta xenotropic and seven different mink cell focus-inducing proviral DNAs. The cloned xenotropic envelope-specific probe was also used in blot hybridization experiments to analyze the arrangement of related sequences in preparations of different mouse liver DNAs.